Process of Renewal of PC&PNDT License of a Large Tertiary Care Teaching Hospital of North India: How One Needs to Plan for It? - Deshikulu, Srivatsa; Sodhi, Jitender; Sharma, Devender Kumar; Madaan, Nirupam; Satpathy, Sidhartha (Indian Journal of Radiology and Imaging, 2024)
Background The Pre-Conception and Pre-Natal Diagnostic Techniques (Prohibition of Sex Selection) Act (PC&PNDT Act), 1994 was enacted to prevent sex determination and female feticide. As a mandatory statutory requirement, All India Institute of Medical Sciences, New Delhi, India has to renew its PC&PNDT license after every 5 years.Aim The current study was undertaken with an objective to delineate in detail, the process of PC&PNDT license renewal, and the challenges dealt with while submitting the renewal application.Methods and Material An observational descriptive study was conducted from February to July 2022. The renewal process was categorized into preapplication, application, and postapplication phases. The requisite documents and data were collected from the Hospital Establishment Section and Medical Records Department.Results The preapplication phase involved obtaining details from 24 departments, with 20 responding initially. Challenges included incomplete documents and deficient details. The application phase required consolidation, affidavits, form filling, and fee payment. Postapplication, an inspection was conducted, and the renewal certification was obtained.Conclusion The study highlights the complexities of renewal of PC&PNDT license of a large multispecialty tertiary care teaching hospital. Planning leads obtained during various phases could serve as a guiding template for other similar teaching hospitals. The study suggests the need for digitalization and streamlining of documentation process to ease out the renewal process and hence contribute to better patient care at large.
Keywords: administrative challenges; female feticide; license renewal; medical institutions; PC&PNDT Act; sex selection